The prelimaries studies on recycled aluminium from automotive component - Mohd Noor, Mazlee; Zulkifli, Abdul Halim; Jamaludin, Shamsul Baharin; Hasan, Shahrizal (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2003)
The research has been carried out using recycled diesel (denoted as Alloy A) and petrol (denoted as Alloy B) aluminium cylinder heads respectively. Sand casting route has been employed to fabricate the specimens. Five specimens have been cast were 100% Alloy A (specimen V), 100% Alloy B (specimen W), 50% Alloy A : 50% Alloy B (specimen X), 70% Alloy A : 30% Alloy B (specimen Y) and 30% Alloy A : 70% Alloy B (specimen Z). Light microscope was used to identify and analyse the microstructure of as-cast alloys. Keller's reagent was used as an etchant in order to reveal the microstructure of the alloys. It has been noted that large dendritic cells were resulted from slow cooling in sand mould. The irregular arrangements of grain boundaries were due to the unmodified process. Typical microstructure has been observed was eutectic aluminium with intermetallics such as Mg2Si, FeSiAls needles and Chinese script particles (Fe,Mn)3Si2Ali5. Less concentrated FeSiAls needles along the grain boundaries had contributed to a higher tensile strength property. For scanning electron microscopy morphology observation, two specimens have been chosen were 100% Alloy B (specimen W) and 30% Alloy A : 70% Alloy B (specimen Z). Both specimens have fractured by tensile test. Specimen W has a higher tensile strength compared to specimen Z. The fracture surface was studied using scanning electron microscope (Leica Cambridge S360 model) in order to characterize the fracture behaviour of the alloys. It was found that specimen W showed the ductile behaviour which exhibited void formations, dimples and shear fractures whereas specimen Z showed the brittle behaviour such as cleavage fractures.